Patterns and trends in European book production and consumption - Kovač, Miha (Javnost (Ljubljana), 2004)
Book publishing is a dark spot in social and media studies. Throughout the twentieth century, statistics on book production, distribution and consumption were inadequate and generated randomly, without properly developed methodology. Even more, in comparison with library science and media studies, book and publishing studies are latecomers to the world of academia: they gain a domestic right there as late as in the last decade of the previous century. Due to this lack of research tradition and methodology, comparisons among different European and between European and American book industries that took place in recent research projects sponsored by the European Union open more questions than they provide answers. At the same time, academic interest in books has been predominantly limited to book and publishing history. The paper will analyse what generated such a state of affairs in recent book research. Further, it will analyse those points that, throughout the 1990s, generated interest in book market research and at the same time produced gaps in the methodology used. In its final pages, the paper will propose some new indicators that might be used in measuring and comparing different book industries.
Keywords: Europe; Evropa; založništvo; knjigotrštvo; knjige; prodaja; trg